Modeling the Way Learning Model in Applying Character Education Values to Early Childhood - Masturin Masturin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study focuses on the “modeling the way” learning model that applies character education values to early childhood. The research was conducted at PAUD Nurul Ilmi, Jati, Kudus, Jawa Tengah with a case study method and a qualitative approach. This research’s informants came from students, teachers, and parents. The results showed that learning by modeling the way on the object of research is carried out through some process, among others: First, the teacher identifies the learning topic. Second, the teacher divides the class into smaller groups with one particular topic being discussed. Third, each group is accompanied to practice on the topics. Fourth, each group demonstrated and provided feedback. The study highlighted that the inculcation of character values from an early age is effective through the “modeling the way” learning model (making practical examples). The contribution of this research is to make references for PAUD educators in carrying out learning